Diplomasi Publik Baru dalam Penyajian Informasi dan Gambaran Budaya Jepang oleh Saluran Youtube ‘only in Japan’ - Putri Mentari Racharjo; R.M.T. Nurhasan Affandi (Padjadjaran Journal of International Relations, 2019)
The emergence of new media raises new forms of diplomacy, which one of them is the new public diplomacy. The emergence of new public diplomacy allows the public to be directly involved in the process of diplomacy. The practice of the new public diplomacy can be seen on Youtube, specifically on the ‘Only in Japan’ channel. This research is aimed to analyze the potrayal of Japanese culture on the Youtube channel "Only in Japan" with new public diplomacy theory. The problem formulated in this research is "What are the characteristics of the new public diplomacy on Youtube channel" Only in Japan? ". This research seeks to describe some of the characteristics of new public diplomacy from various international relations students that can be found on the Youtube channel 'Only in Japan'. In an effort to examine and understand this problem, researchers use qualitative methods by collecting data through interviews, literature studies, and online searches. This research shows that there are eight characteristics of the new public diplomacy on Youtube channel 'Only in Japan'. Not only does it contribute to Japan's branding to the global community, 'Only in Japan' Youtube channel also builds an interactive relationship with the global community.   Kemunculan media baru memunculkan bentuk-bentuk baru dari diplomasi, salahsatunya adalah diplomasi publik baru. Kemunculan diplomasi publik baru memungkinkan masyarakat untuk terlibat langsung dalam proses diplomasi. Salah satu praktik diplomasi publik baru dapat dilihat pada Youtube, secara khusus saluran Only in Japan. Riset ini ditujukan untuk melihat penyajian budaya Jepang dalam saluran Youtube ‘Only in Japan’ dengan teori diplomasi publik baru. Masalah yang dirumuskan dalam riset ini adalah “Karakteristik apa yang meMerupakan diplomasi publik baru dalam saluran Youtube ‘Only in Japan’?”. Riset ini berusaha untuk mendeskripsikan beberapa karakteristik diplomasi publik baru dari para penstudi hubungan internasional yang dapat terdapat dalam saluran Youtube ‘Only in Japan’. Dalam upaya mengkaji dan memahami masalah ini, periset menggunakan metode kualitatif dengan pengumpulan data melalui wawancara, studi pustaka, dan penelusuran daring. Riset ini menunjukan bahwa terdapat delapan karakteristik diplomasi publik baru dalam saluran Youtube ‘Only in Japan’. Tidak hanya berkontribusi dalam branding Jepang terhadap masyarakat global, saluran ‘Only in Japan’ juga membangun hubungan interaktif dengan masyarakat global.